Identifying the optimal donor for natural killer cell adoptive therapy to treat paediatric B‐ and T‐cell acute lymphoblastic leukaemia. Issue 7 (16th July 2020) - Foley, Bree; Ta, Clara; Barnes, Samantha; de Jong, Emma; Nguyen, Michelle; Cheung, Laurence C; Buzzai, Anthony; Wagner, Teagan; Wylie, Ben; Fernandez, Sonia; Cruickshank, Mark; Endersby, Raelene; et al.
Abstract: Objectives: Natural killer (NK) cells are an attractive source of cells for an 'off the shelf' cellular therapy because of their innate capacity to target malignant cells, and ability to be transferred between donors and patients. However, since not all NK cells are equally effective at targeting cancer, selecting the right donor for cellular therapy is critical for the success of the treatment. Recently, cellular therapies utilising NK cells from cytomegalovirus (CMV)‐seropositive donors have been explored. However, whether these NK cells are the best source to treat paediatric acute lymphoblastic leukaemia (ALL) remains unclear. Methods: Using a panel of patient‐derived paediatric B‐ and T‐ALL, we assessed the ability of NK cells from 49 healthy donors to mount an effective functional response against these two major subtypes of ALL. Results: From this cohort, we have identified a pool of donors with superior activity against multiple ALL cells. While these donors were more likely to be CMV +, we identified multiple CMV neg donors within this group. Furthermore, NK cells from these donors recognised B‐ and T‐ALL through different activating receptors. Dividing functional NK cells into 29 unique subsets, we observed that within each individual the same NK cell subsets dominated across all ALL cells. Intriguingly, this occurred despite the ALL cells in our panel expressing different combinations of NK cell ligands. Finally, we can demonstrate that cellular therapy products derived from these superior donors significantly delayed leukaemia progression in preclinical models of ALL. Conclusions: We have identified a pool of superior donors that are effective against a range of ALL cells, representing a potential pool of donors that can be used as an adoptive NK cell therapy to treat paediatric ALL. Abstract : Natural killer (NK) cells are an attractive source of cells for an 'off the shelf' cellular therapy; however, since not all NK cells are equally effective at targeting cancer, selecting the right donor for cellular therapy is critical for the success of the treatment. We identified a group of donors who exhibited superior responses against multiple acute lymphoblastic leukaemia (ALL) cells, representing a potential pool of donors that could be used to develop an adoptive NK cell therapy capable of treating a range of ALL subtypes.